2001
DOI: 10.1379/1466-1268(2001)006<0136:tnmiat>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear matrix is a thermolabile cellular structure

Abstract: Heat shock sensitizes cells to ionizing radiation, cells heated in S phase have increased chromosomal aberrations, and both Hsp27 and Hsp70 translocate to the nucleus following heat shock, suggesting that the nucleus is a site of thermal damage. We show that the nuclear matrix is the most thermolabile nuclear component. The thermal denaturation profile of the nuclear matrix of Chinese hamster lung V79 cells, determined by differential scanning calorimetry (DSC), has at least 2 transitions at Tm = 48 degrees C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 43 publications
4
34
1
Order By: Relevance
“…It has been suggested that intranuclear inclusion formation of polyQ-expanded ATXN3 is promoted by the nuclear environment (11), and in fact, heat-induced denaturation of proteins is more rapid in the nuclear compartment compared with the cytoplasm, as demonstrated by biophysical (28) and biochemical (29,30) experiments. On the other hand, evidence has been provided that nuclear inclusions are active proteolytic centers (31).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that intranuclear inclusion formation of polyQ-expanded ATXN3 is promoted by the nuclear environment (11), and in fact, heat-induced denaturation of proteins is more rapid in the nuclear compartment compared with the cytoplasm, as demonstrated by biophysical (28) and biochemical (29,30) experiments. On the other hand, evidence has been provided that nuclear inclusions are active proteolytic centers (31).…”
Section: Discussionmentioning
confidence: 99%
“…(29) The activation energeries for protein denaturization and heat induced cell death were noted to be within the same range. Further research suggested that nuclear proteins are most sensitive (30)(31)(32) and a high degree of correlation of nuclear protein aggregation and heat induced cell kill has been noted. Radiation sensitization is achieved in large part through nuclear protein aggregation which inhibits the DNA repair process thus converting potentially lethal radiation induced DNA breaks into lethal events.…”
Section: Mechanism Of Cell Death With Hyperthermiamentioning
confidence: 99%
“…Induced Hsp70 protects cells, tissues, and organisms against damage from a wide variety of stressful stimuli (Hightower, 1991;Niu et al, 2006;Wu et al, 1996Wu et al, , 2001. Hsp70 can translocate to the nucleus and accumulate there under heat shock or in other harmful conditions (Chughtai et al, 2001;Lepock et al, 2001;Szekely et al, 1995). However, the potential role of Hsp70 in the regulation of the response to some carcinogenic reagents, such as benzo[a]pyrene (BaP), remains unclear.…”
Section: Introductionmentioning
confidence: 99%